How Can We Do Better? Learning From 617 Pediatric Patients With Airway Foreign Bodies Over a 2-Year Period in an Asian Population - Gao, Ying-Qin; Tan, Jian Li; Wang, Mei-Lan; Ma, Jing; Guo, Jia Xi; Lin, Ken; Wei, Jing-Juan; Wang, De-Yun; Zhang, Tie-Song (Frontiers in Pediatrics, 2020)
Background: Foreign body (FB) in the pediatric airway is a prevailing and crucial emergency with presenting symptoms often overlapping with other common pediatric conditions. There are limited number of large cohort studies in an Asian population which demonstrate the diversity of symptoms, investigations which will aid in obtaining the diagnosis, and management. Using this large cohort, we aim to evaluate the type and location, clinical presentations and outcomes of medical management related to pediatric airway FB in an Asian society. Methods: This is a retrospective study of all airway FB treated in Kunming Children's Hospital, China from February 2016 to June 2019. Six hundred and thirty-two clinical and operative records of all airway FB were retrieved and reviewed from the hospital's central electronic medical records. A total of 617 patients were included in our study. Results: The age ranged from 4 months to 12 years (mean = 1.74 years). The duration of symptoms ranged from 1 h to 605 days, with the diagnosis established at an average 9.16 days. Almost all had multiple symptoms, most commonly cough (98.5%) followed by noisy breathing (98.2%). Majority of the FBs (95.5%) were organic and the rest inorganic. Of the organic FBs, peanut was the most common (31.6%), followed by walnut (13.3%) and sunflower seeds (9.2%). Comparatively, 80.8% of the organic FBs were retrieved incomplete while 85.7% of the inorganic FBs were completely intact. Multiple FBs were noted in 43.3% of the patients, with 2.4% of them in different locations. Conclusions: Airway FB can be easily missed with resultant delay in diagnosis. In an Asian population, walnut and sunflower/pumpkin seeds feature more prominently compared to Western populations. Sunflower seed FBs tend to present earlier and are found intact in the trachea. Rigid bronchoscopy is the most common technique used to remove such FBs and pulmonary-related complications post-operatively, though rare, are the most common adverse outcomes. Preventive strategies targeting the appropriate age group and this type of FB may be useful in an Asian population.